An investigation on students’ e-learning readiness in higher education - Maya Marsevani (Universitas PGRI Semarang, 2021)
The main goal of this research was to measure students’ readiness in applying E-Learning. Quantitative method was employed in this research. The researcher distributed an online questionnaire to undergraduate students at one of private university in Batam randomly. The collected data was analyzed with statistical software SPSS. The descriptive statistics (percentage, means and standard deviations) were calculated and reported in this research. Four categories of students’ readiness are being discussed in this research – students’ technology skills, technology access, motivation, and time management. Based on the result, the students were highly ready learn using E-Learning with overall mean 3.34